2018
DOI: 10.1007/s10517-018-4242-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNA Potentially Regulated by AhR and CAR in Malignant Tumors of the Endometrium

Abstract: We studied microRNA whose expression can be regulated by carcinogenic compounds. Bioinformatic analysis has detected microRNA potentially regulated by xenosensor receptors AhR (miR-28, miR-30c, miR-30e, miR-139, and miR-153) and CAR (miR-29c, miR-31, miR-185, miR-625, and miR-652). Published data indicate that these microRNAs are oncosuppressors, except miR-31 that can act as an oncogene. The expression of these microRNAs in malignant tumors of the endometrium was studied. The expression of the majority of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Our literature review identified 30 articles studying the expression pattern of miR in neoplastic endometrial tissue compared to in benign and/or hyperplastic tissues [13,14,23,24,25,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52]. The studies included an average of 45 endometrial tumor samples (minimum 7, maximum 141), with well-defined histological types for 15 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review identified 30 articles studying the expression pattern of miR in neoplastic endometrial tissue compared to in benign and/or hyperplastic tissues [13,14,23,24,25,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52]. The studies included an average of 45 endometrial tumor samples (minimum 7, maximum 141), with well-defined histological types for 15 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, AhR has been shown to prevent tumor development through the regulation of several tumor suppressor miRNAs in breast cancer [61], prostate cancer [62], and malignant tumors of the endometrium [63].…”
Section: Ahr As a Tumor Suppressormentioning
confidence: 99%
“…This systematic review identified 105 original articles and two literature reviews reporting the expression pattern of miRNAs . Of the 69 articles comparing neoplastic endometrial tissue with the surrounding healthy tissue, 39 were published after October 31, 2018 and were not presented in our previous review [53][54][55][56][57][58][59]94,96,[98][99][100][101][102][103][131][132][133][134]. Overall, the 69 studies included an average of 82 endometrial tumor samples (minimum 4, maximum 579) and 22 healthy endometrial samples (minimum 5, maximum 56).…”
Section: Expression Profile Of Mirnas Of Epigenetic Modifiers Associated With Malignant Endometrial Tissue Compared With Healthy Endometrmentioning
confidence: 99%